Learning Short Story Writing by Quantum Model for Eleventh Graders based on Learning Styles - Sa?adah, Nurus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Writing a short story by learners needs to consider formative elements. Therefore, it needs appropriate and suitable learning model for their learning styles. This research aims to analyze the effectiveness of writing short story learning with a quantum model based on learning styles of eleventh graders of senior high school. This pseudo-experimental research used written short story writing test, learning style test, attitude observation, photographs, and interview as techniques of collecting data. Normality test is done by using the Kolmogorov Smirnov test. Homogeneity test of the data used Levense. Hypothesis test used paired sample t-test. All of them were done by using SPSS 20 program. It is concluded that the implementation of the model is effective in learning short story writing based on the learning styles of the students. The learning by using the model is more effective for kinesthetic learning style than visual and auditory learning styles. This research is expected to contribute to developing educational field research and to enrich the knowledge of short story writing in an educational institution.